Root resorption followed by orthodontic treatment in individuals with anterior open bite. A complete vision focused on different treatment alternatives: A review - Ramirez-Diaz, Ruth Elizabeth (2022)
The aim of this review was to determine the incidence of different types of treatment and the prevalence of root resorption in incisors induced by orthodontic treatment in patients with open bite. Libraries and electronic databases were searched, with 322 articles being selected and 55 articles considered regarding the PRISMA checklist. It has been shown that apical root resorption of the incisors is more frequent in patients with premolar extractions than in those treated without extractions, due to greater apical displacement during retraction of the anterior teeth in the space closure phase. On the other hand, it has been described that intrusion of posterior teeth is four times more likely to cause root resorption than extrusion movement, thereby increasing the risk of root resorption in posterior teeth compared to conventional orthodontic treatment not requiring molar intrusions. Finally, aligners, such as orthodontic treatments with fixed appliances, have not been shown to induce clinically significant root resorption in open-bite individuals. Literature on root resorption in open bite treatments is scarce making difficult conclusions difficult. However, the amount of root loss in cases of open bite seems to be similar to that of individuals without an open bite.